Yakov Yakovych Belen de Ballu (1753–1815) – professor of Kharkiv University, first librarian of the university library. - Глибицька, Світлана; Bobrova, Maryna; Fedorenko, Vitalina (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2024)
Purpose. To trace the life and creative path of Ya. Ya. Belin de Ballu (1753–1815), a writer, translator, professor of the department of classical philology and at the same time the first librarian of the newly established Imperial Kharkiv University; to publicize the portrait of Ya. Ya. Belin de Ballu, which was found in 2023 almost 220 years after the scientist worked at Kharkiv University.Research methodology is based on the principles of historicism, objectivity and systematicity.Scientific novelty. For the first time, the most complete information about Ya. Ya. Belin de Ballu, which is reflected in domestic and international sources, has been collected; a portrait of a scientist presented to the scientific community for the first time.Conclusions. Ya. Ya. Belin de Ballu is one of the organizers of Kharkiv University and its library, one of the first professors and the first librarian of the university library. Among his many services to the university and the library is that he compiled and published a catalog of Greek manuscripts from the 12th to 18th centuries, which are kept in the university library, and compiled a Latin anthology that was published in the university printing house.